Violence against women as conveyed by surveys - the Finnish case - Piispa, Minna (Journal of Scandinavian studies in criminology and crime prevention, 2003)
The methodological choices made in a survey may partly shape the picture a survey conveys of partnership violence. This article considers some of the choices made in the Finnish survey on violence against women, such as the way the violence was defined and how the definition tried to take into account the special characteristics of this kind of violence, in order to help the respondents to identify and recall different events of it. The empirical analyses showed that the used definition of violence had not reached all the respondents representing different population groups. The experiences of partner violence among older, less educated women, and the experiences of those who felt embarrassed or ashamed to speak about issues concerning their partner or partnership, were more probably under-represented in the survey